Advanced and sustainable manufacturing methods of polymer-based membranes for gas separation: a review - Alkandari, Sharifah H.; Castro-Dominguez, Bernardo (Frontiers in Membrane Science and Technology, 2024)
The fabrication of membranes for gas separation presents challenges that hinder their deployment as a truly sustainable technology. This review systematically explores the evolution and advancements in materials and manufacturing methods of polymer-based membranes, with a keen emphasis on sustainability and efficiency. The review delineates a broad spectrum of manufacturing techniques, ranging from traditional methods to cutting-edge approaches such as layer-by-layer assembly, and green synthesis, highlighting their implications for environmental sustainability, performance enhancement, scalability, and economic viability. Key findings indicate a significant shift towards greener solvents, biobased polymers and processes that reduce waste and costs. Critical analysis uncovers a growing focus on understanding the life cycle of membranes and developing strategies for end-of-life such as recycling and the use of biodegradable materials, underscoring the commitment of the community to minimizing environmental footprints.